Extracellular Vesicle-Dependent Cross-Talk in Cancer—Focus on Pancreatic Cancer - Nannan, Lise; Oudart, Jean-Baptiste; Monboisse, Jean Claude; Ramont, Laurent; Brassart-Pasco, Sylvie; Brassart, Bertrand (Frontiers in Oncology, 2020)
Extracellular vesicles (EVs), such as exosomes and shed microvesicles are generated by many different cells. However, among all cells, cancer cells are now recognized to secrete more EVs than healthy cells. Tumour-derived EVs can be isolated from biofluids such as blood, urine, ascitic fluid and saliva. Their numerous components (nucleic acids, proteins, lipids) possess many pleiotropic functions involved in cancer progression. The tumour-derived EVs generated under the influence of the tumour microenvironment play distant roles and promote cellular communication by directly interacting with different cells. Moreover, they modulate extracellular matrix remodeling and tumour progression. Tumour-derived EVs are involved in pre-metastatic niche formation, which is dependent on EV-associated protein receptors, and in cancer chemoresistance as they transfer drug-resistance-related genes to recipient cells. Recent advances in preclinical and clinical fields suggest their potential use as biomarkers for diagnosis and prognosis as well as for drug delivery in cancer. In this review, we discuss EV characteristics and pro-tumour capacities, and highlight the future crucial impact of tumour-derived EVs in pancreatic cancer diagnosis and prognosis.